Longitudinal Effects of a Second-Order Multi-Problem Factor of Sexual Risk, Marijuana Use, and Delinquency on Future Arrest Among Truant Youths. Issue 6 (1st November 2016) - Dembo, Richard; Wareham, Jennifer; Schmeidler, James; Winters, Ken C.
ABSTRACT: Based on problem-behavior theory (Jessor & Jessor, 1977 ), a second-order problem behavior model of delinquency, marijuana use, and risky sexual behavior over five waves was estimated among truant adolescents. The study also investigated the influence of the problem factor on future arrest charges and the effect of sociodemographics on problem behavior and future crime. Results confirm the existence of a second-order latent factor of problem behaviors. Problem behaviors predicted more future arrest charges. Age was related to problem behaviors and future arrest charges, and family income was related to problem behavior. Implications for future research and practice are discussed.